Application of Panel Regression Model in Gender Studies in East Java - Pardomuan Robinson Sihombing; Ade Marsinta Arsani; I Gede Heprin Prayasta; Ida Ayu Candrawati (Future Science, 2023)
Gender inequality remains one of the exciting issues to discuss. The role of women in social and economic continues to increase from year to year. This study aims to see the effect of the Gender Empowerment Index (GEI), Gender Development Index (GDI), and poverty rate on the Gender Inequality Index (GII) in East Java. Data sourced from the BPS-Statistics Indonesia of East Java Province for the 2018-2020 period. The statistical method used was multiple linear regression with panel data. Based on panel model testing, the random model is the best. Simultaneously, all variables affect the GII. Partially, GEI and GDI have a significant negative effect on GII. On the other hand, the percentage of poor people has a significant positive effect on GII. Based on the results of this study, comprehensive policies related to macro-social economics are needed so that the level of GII continues to decline.